Role of Sulfur Metabolism Gene and High-Sulfur Gene Expression in Wool Growth Regulation in the Cashmere Goat - Chai, Yuan; Sun, Yanyong; Liu, Bin; Guo, Lili; Liu, Zaixia; Zhou, Le; Dai, Lingli; Jia, Chunyan; Zhang, Wenguang; Li, Chun (Frontiers in Genetics, 2021)
Abstract: Sulfur, an essential mineral element for animals, mainly exists in the form of organic sulfur-containing amino acids (SAAs), such as cystine, methionine, and cysteine, within the body. The content, form, and structure of sulfur play an important role in determining the wool fiber quality. In addition, keratin-associated proteins, one of the most crucial wool fiber components, are rich in SAAs. However, sulfur metabolism from the blood to the skin and hair follicles remains unclear. In this study, we analyzed high-sulfur protein gene and sulfur metabolism genes in the cashmere goat and explored the effects of melatonin on their expression. In total, 53 high-sulfur protein genes and 321 sulfur metabolism genes were identified. We found that high-sulfur protein genes were distributed in the 3M–4M and 144M regions of chromosome 1 and the 40M–41M region of chromosome 19 in goats. Moreover, all year round, allele-specific expression (ASE) is higher in the 40M–41M region of chromosome 19 than in the other regions. Total of 47 high-sulfur protein genes showed interaction with transcription factors and cofactors with ASE. These transcription factors and cofactors were inhibited after melatonin implantation. The network analysis revealed that melatonin may activate the sulfur metabolism process via the regulation of the genes related to cell energy metabolism and cell cycle in the skin, which provided sufficient SAAs for wool and cashmere growth. In conclusion, our findings provide a new insight into wool growth regulation by sulfur metabolism genes and high-sulfur protein genes in cashmere goats.